Venom from Opisthacanthus elatus scorpion of Colombia, could be more hemolytic and less neurotoxic than thought (2016)
We report the first biochemical, biological, pharmacological and partial proteomic characterization studies of the Opisthancanthus elatus venom (Gervais, 1844) from Colombia. The Reverse Phase High-Performance Liquid Chromatography venom profile showed 28 main well-defined peaks, most eluting between 20 and 45min (18-30% of acetonitrile, respectively). High-resolution mass analysis indicates the presence of 106 components ranging from 806.59742Da to 16849.4139Da. O. elatus venom showed hemolytic activity and hydrolyzed the specific substrate BapNa suggesting the presence of proteins with serine-protease activity. Collected RP-HPLC fractions eluting at 52.6, 55.5, 55.8, 56.2, and 63.9min (PLA2 region between 33 and 40% of acetonitrile), showed hemolytic activity and hydrolyzed the synthetic substrate 4-nitro-3-octanoyloxy-benzoic acid, indicating the presence of compounds with phospholipases A2 activity. These RP-HPLC fractions, showed molecular masses values up to 13978.19546Da, corroborating the possible presence of the mentioned enzymes. Tryptic digestion and MS/MS analysis showed the presence of a phospholipase like fragment, similar to on described in other Opisthacanthus genus studies. No coagulant activity was observed. No larvicidal or antimicrobial activity was observed at concentrations evaluated. Lethal and toxic activity is expected at doses above 100mg/kg, no neurotoxic effects were detected at lower doses. In conclusion, O. elatus exhibits a venom with a predominant phospholipase A2 activity than thought; mammal's neurotoxic activity is expected above the 100mg/kg, which is very high compared to the venom from other neurotoxic scorpions. © 2015 Elsevier B.V.